Pengaruh Program Corporate Social Responsibility Terhadap Tingkat Kesejahteraan dan Lingkungan Sekitar PT Hindoli di Musi Banyuasin dan Banyuasin Sumatera Selatan - Edi Irianto; Rosyani Rosyani; Edison Edison (Universitas Jambi, 2022)
This study aims to determine the programs of Corporate Social Responsibility activities, what are the Corporate Social Responsibility programs that influence and the environment and to analyze the great Corporate Social Responsibility programs on the environment and environment around PT Hindoli in Musi Banyuasin and Banyuasin Regencies in South Sumatra Province. PT Hindoli's Corporate Social Responsibility Program is considered in four areas, namely education, health, environmental and community empowerment and infrastructure. This study uses Chi-Square analysis method. The results of Chi-Square analysis show that the Corporate Social Responsibility program is in the field of education (3,135), health (2,403), environment (3,4) and also in community empowerment and infrastructure (2,114) and the environment around PT Hindoli. Based on the partial test, the tcount value is 2,349 which means that there is a difference between PT Hindoli's Corporate Social Responsibility program on the level of welfare and the surrounding environment. The results showed that 82% of the level of welfare and environment in the study area could be influenced by PT Hindoli's Corporate Social Responsibility program. Thus it can be concluded that the joint program of PT Hindoli's Corporate Social Responsibility in the field of education, health, environment and the field of community empowerment and infrastructure affect and the environment in the research area.